Blade-Coated Porous 3D Carbon Composite Electrodes Coupled with Multiscale Interfaces for Highly Sensitive All-Paper Pressure Sensors - Zheng, Bowen; Guo, Ruisheng; Dou, Xiaoqiang; Fu, Yueqing; Yang, Bingjun; Liu, Xuqing; Zhou, Feng (Nano-Micro Letters, 2024)
Flexible and wearable pressure sensors hold immense promise for health monitoring, covering disease detection and postoperative rehabilitation. Developing pressure sensors with high sensitivity, wide detection range, and cost-effectiveness is paramount. By leveraging paper for its sustainability, biocompatibility, and inherent porous structure, herein, a solution-processed all-paper resistive pressure sensor is designed with outstanding performance. A ternary composite paste, comprising a compressible 3D carbon skeleton, conductive polymer poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate), and cohesive carbon nanotubes, is blade-coated on paper and naturally dried to form the porous composite electrode with hierachical micro- and nano-structured surface. Combined with screen-printed Cu electrodes in submillimeter finger widths on rough paper, this creates a multiscale hierarchical contact interface between electrodes, significantly enhancing sensitivity (1014 kPa−1) and expanding the detection range (up to 300 kPa) of as-resulted all-paper pressure sensor with low detection limit and power consumption. Its versatility ranges from subtle wrist pulses, robust finger taps, to large-area spatial force detection, highlighting its intricate submillimeter-micrometer-nanometer hierarchical interface and nanometer porosity in the composite electrode. Ultimately, this all-paper resistive pressure sensor, with its superior sensing capabilities, large-scale fabrication potential, and cost-effectiveness, paves the way for next-generation wearable electronics, ushering in an era of advanced, sustainable technological solutions. Highlights: 1 A blade-coated composite paste, composed of a compressible 3D carbon skeleton, PEDOT:PSS, and CNTs, can naturally dry to form a porous electrode on paper with a micro- and nano-structured surface. 2 The all-paper pressure sensor demonstrated an ultrahigh sensitivity of 1014 kPa−1, a wide responsive range up to 300 kPa, and an ultralow operating voltage of 0.01 V. 3 The sensor showcased superior detection capability, ranging from subtle wrist pulses and robust finger taps to large-area spatial force.